Logit price dynamics - James Costain; Anton Nakov (European Central Bank (ECB), 2014)
We model retail price stickiness as the result of errors due to costly decision-making. Under our assumed cost function for the precision of choice, the timing of price adjustments and the prices firms set are both logit random variables. Errors in the prices firms set help explain micro “puzzles” relating to the sizes of price changes, the behavior of adjustment hazards, and the variability of prices and costs. Errors in adjustment timing increase the real effects of monetary shocks, by reducing the “selection effect”. Allowing for both types of errors also helps explain how trend inflation affects price adjustment.
Keywords: E31; D81; C73; 330; information-constrained pricing; logit equilibrium; near rationality; nominal rigidity; state-dependent pricing